2020
DOI: 10.7150/ijms.39523
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral anticoagulants and osteoporosis: Real-world data mining using a multi-methodological approach

Abstract: Introduction: Warfarin and direct oral anticoagulants (DOACs) have been widely used in antithrombotic therapy. Although warfarin use has been suspected to be associated with osteoporosis risk, several studies have shown otherwise. Conversely, a few reports have found an association between DOACs and osteoporosis. This study therefore clarifies the association between oral anticoagulants and osteoporosis by analyzing real-world data using different methodologies, algorithms, and databases. Methods: Real-world d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…Our results are similar to the multi-methodological data mining analysis from real-world data analysis from the US Food and Drug Administration Event Reporting System and Japanese administration claims database, which revealed that warfarin use, not DOACs, is significantly associated with osteoporosis or use of bisphosphonate regardless of sex difference. [ 22 ] In our meta-analysis, the age, the proportion of female gender, chronic kidney disease, and osteoporosis were similar between the DOAC and VKA groups. Signorelli et al [ 3 ] compared the effect of heparin, VKA, and DOACs in bone metabolism.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our results are similar to the multi-methodological data mining analysis from real-world data analysis from the US Food and Drug Administration Event Reporting System and Japanese administration claims database, which revealed that warfarin use, not DOACs, is significantly associated with osteoporosis or use of bisphosphonate regardless of sex difference. [ 22 ] In our meta-analysis, the age, the proportion of female gender, chronic kidney disease, and osteoporosis were similar between the DOAC and VKA groups. Signorelli et al [ 3 ] compared the effect of heparin, VKA, and DOACs in bone metabolism.…”
Section: Discussionmentioning
confidence: 73%
“…[3] There have been some head-to-head comparisons of VKA and DOACs in terms of efficacy and safety, which have data on osteoporosis and fracture risk. [13][14][15][16][17][18][19][20][21][22][23] We have conducted a network analysis to compare the risk of osteoporotic fracture in nonvalvular AF (NVAF) patients taking oral anticoagulants (OAC; viz VKA, Dabigatran, Rivaroxaban, Apixaban, and Edo xaban).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report that has examined the relationship of medication use with fracture nonunion in persons with a SCID and found no significant association of any medication examined, including anticoagulants, opioids, anticonvulsants, benzodiazepines, or antidepressants with fracture nonunion. Warfarin (24) and antidepressants (25) have been associated with fracture risk in elderly able-bodied individuals, although the relationship of antidepressant use to fracture varies by antidepressant class and specific drug used. (25) Opioids, benzodiazepines, and anticonvulsants are frequently used by persons with a SCID and are significantly related to fracture risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 14, 2020. . https://doi.org/10.1101/2020.04.10.20061358 doi: medRxiv preprint 5 AEs, it is widely used in identifying potential link between drugs and AEs during post-marketing surveillance of drug safety, [10], despite the risk of bias that is associated with its self-reported data [11].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…In the current study, we investigated the link between the use of chloroquine and the occurrence of neuropsychiatric symptoms, using the FDA Adverse Event Reporting System (FAERS) database that is provided by the FDA [9]. Since this database contains a very large number of case reports of drug AEs, it is widely used in identifying potential link between drugs and AEs during post-marketing surveillance of drug safety, [10], despite the risk of bias that is associated with its self-reported data [11].…”
Section: Introductionmentioning
confidence: 99%